2018
DOI: 10.1088/1748-9326/aab89c
|View full text |Cite
|
Sign up to set email alerts
|

Increased importance of methane reduction for a 1.5 degree target

Abstract: To understand the importance of methane on the levels of carbon emission reductions required to achieve temperature goals, a processed-based approach is necessary rather than reliance on the transient climate response to emissions. We show that plausible levels of methane (CH 4 ) mitigation can make a substantial difference to the feasibility of achieving the Paris climate targets through increasing the allowable carbon emissions. This benefit is enhanced by the indirect effects of CH 4 on ozone (O 3 ). Here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 30 publications
1
72
0
2
Order By: Relevance
“…decline noted above suggests cooling relative to the current temperature ( figure 5(b), see [16] for discussion of the physical origin and uncertainty in this rate of decline). This is broadly the role of methane in ambitious mitigation pathways, where significant, permanent, reductions in methane emission rates can permit the emissions of a fixed amount of extra CO 2 , and hence the additional long-term warming it will cause, under a given temperature ceiling [35,36]. This concept is explored further below when demonstrating the use of GWP * to assess alternative mitigations.…”
Section: Stable and Declining Methane Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…decline noted above suggests cooling relative to the current temperature ( figure 5(b), see [16] for discussion of the physical origin and uncertainty in this rate of decline). This is broadly the role of methane in ambitious mitigation pathways, where significant, permanent, reductions in methane emission rates can permit the emissions of a fixed amount of extra CO 2 , and hence the additional long-term warming it will cause, under a given temperature ceiling [35,36]. This concept is explored further below when demonstrating the use of GWP * to assess alternative mitigations.…”
Section: Stable and Declining Methane Emissionsmentioning
confidence: 99%
“…The 'stock' component, respresenting the longterm temperature adjustment to methane emissions, is still important, and the scale of contemporary methane emissions is such that this element could equate to a significant increase in total allowable CO 2 emissions for warming of 1.5°C if action is taken on methane earlier rather than later [35], but by a much smaller amount than the direct GWP 100 equivalence between methane and CO 2 would suggest. Figure 8.…”
Section: Increasing Methane Emissionsmentioning
confidence: 99%
“…This concept was introduced into metrics in Allen et al (2016) where they used a single number (GWP X (100)×100) to equate permanent step changes in SLCF emissions to a one-off pulse emission of CO 2 . Collins et al (2018) calculated the impact of methane mitigation on allowable carbon budgets. Using a simple climate model coupled to a carbon cycle model, they showed that for a fixed temperature target, a step reduction in methane emissions of 1 Gt(CH 4 ) yr −1 was approximately equivalent to an increase in allowed cumulative CO 2 emissions of 2900-3300 Gt(CO 2 ).…”
Section: Metric Designmentioning
confidence: 99%
“…Primary among these are estimates of available carbon emission budgets commensurate with limiting global warming below specific targets (Matthews et al, 2017). Introducing prognostic atmospheric chemistry into GC3.1 allows an assessment of the mitigation potential from reducing short lived climate forcers such as methane, black carbon, and tropospheric ozone (Collins et al, 2018;Stohl et al, 2015), while coupling atmospheric chemistry to terrestrial biogeochemistry opens up the potential to study the risk of permafrost thaw, methane release, and their impacts on Arctic warming. A full atmosphere treatment of ozone chemistry supports a joined-up study of stratospheric ozone recovery and climate change as well as analysis of interactions between climate warming, tropospheric ozone, and vegetation (Sadiq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%